Vpliv Santorijevih del na Dubrovčana Đura Armena Baglivija - Zupanič Slavec, Zvonka (Medicinski razgledi, 2001)
Santorio Santorio (1561-1636), a physician born in Capodistria, introduced newworth into medicine with his quantitative approach. The possibility of numeric monitoring and measuring various physiological and pathological processes within the human body, i.e. metabolism or recording of body temperature, brought exactness in expression into medicine, along with the possibility of proving results. Santorio was Galileos pupil and accepted his mechanistic principles, introducing them in his work De medicina statica. His work influenced many generations of physicians. This article mainly discusses Santorios influence on Baglivi, a physician from Dubrovnik.
Keywords: History of medicine, 17th cent.; Santorio, Santorio, 1561-1636; History of medicine, 18th cent.; Baglivi, Djuro Armen, 1668-1707; Bibliografija; Biography; Bibliography; Biografija; Croatia; Zgodivina medicine 18. stoletja; Zgodovina medicine 17.stoletja; Hrvaška; zgodovina medicine; biografije